Unilateral eyelid angioedema: An atypical manifestation in childhood IgA vasculitis - R Deepashree; Arakali Lakshminarayana Shyam Prasad (Wolters Kluwer Medknow Publications, 2023)
Immunoglobulin A (IgA) vasculitis (Henoch-Schönlein purpura) is an immune-mediated small vessel vasculitis, in which edema of the nondependent areas of the body, including the face and scalp is a rare cutaneous finding, found mostly in children <2 years of age. We report a case of a 7-year-old girl presenting with unilateral eyelid angioedema as a manifestation of IgA vasculitis. Early diagnosis and treatment are necessary, as the risk of renal complications increases with the incidence of angioedema.